2009
DOI: 10.1016/j.neuron.2009.06.007
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Cocaine Experience Generates Silent Synapses

Abstract: Summary Studies over the past decade have enunciated silent synapses as prominent cellular substrates for synaptic plasticity in the developing brain. However, little is known about whether silent synapses can be generated post-developmentally. Here, we demonstrate that highly salient in vivo experience, such as exposure to cocaine, generates silent synapses in the nucleus accumbens (NAc) shell, a key brain region mediating addiction-related learning and memory. Furthermore, this cocaine-induced generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
370
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 241 publications
(394 citation statements)
references
References 39 publications
(70 reference statements)
18
370
6
Order By: Relevance
“…In NAc shell MSNs, laser stimulation (467 μm, 0.1-1 ms) evoked EPSCs, which were presumably from ChR2-expressing PVT-to-NAc synapses. A minimal stimulation assay (Isaac et al, 1995;Liao et al, 1995;Huang et al, 2009) revealed that silent synapse levels were significantly increased within this projection (Figure 2a-c; t(25) = 2.69, po0.05, saline 21.27 ± 8.08%, cocaine 47.03 ± 5.60%). We also noted that the basal (saline) levels of silent synapses (~20%) appear to be higher in this projection than other NAc projections (o10%) previously examined in age-matched rats Ma et al, 2014).…”
Section: Altered Properties Of Pvt-to-nac Synapses 1-2 D After Cocainmentioning
confidence: 96%
See 2 more Smart Citations
“…In NAc shell MSNs, laser stimulation (467 μm, 0.1-1 ms) evoked EPSCs, which were presumably from ChR2-expressing PVT-to-NAc synapses. A minimal stimulation assay (Isaac et al, 1995;Liao et al, 1995;Huang et al, 2009) revealed that silent synapse levels were significantly increased within this projection (Figure 2a-c; t(25) = 2.69, po0.05, saline 21.27 ± 8.08%, cocaine 47.03 ± 5.60%). We also noted that the basal (saline) levels of silent synapses (~20%) appear to be higher in this projection than other NAc projections (o10%) previously examined in age-matched rats Ma et al, 2014).…”
Section: Altered Properties Of Pvt-to-nac Synapses 1-2 D After Cocainmentioning
confidence: 96%
“…We thus measured the ratio of the amplitudes of AMPAR-and NMDAR-mediated EPSCs at PVT-to-NAc synapses. AMPAR EPSCs were optogenetically elicited (stimulation duration, 0.1-1.5 ms) at − 70 mV, while NMDAR EPSCs were elicited at +50 mV with the current amplitude 40 ms after the current peak defined as the amplitude of NMDAR EPSCs (at this time point, minimal AMPAR-mediated components are active) (Huang et al, 2009). One-to-2 days after cocaine selfadministration, the AMPAR/NMDAR ratio was significantly decreased (Figure 2d and e; t(11) = 2.53, po0.05, saline 2.21 ± 0.69, cocaine 0.58 ± 0.09), consistent with the above results, indicating that the portion of NMDAR-only synapses is significantly increased.…”
Section: Altered Properties Of Pvt-to-nac Synapses 1-2 D After Cocainmentioning
confidence: 99%
See 1 more Smart Citation
“…Failures and responses at − 75 mV (F − 75 ) and at +40 mV (F +40 ) were identified by visual analysis of traces. The fraction of silent synapses was calculated using an equation: 1 − Ln (F − 75 )/Ln(F +40 ) (Huang et al, 2009). …”
Section: Electrophysiologymentioning
confidence: 99%
“…Recently, new silent synapses were found in the adult brain after exposure to cocaine (Huang et al, 2009;Koya et al, 2012), trauma (Lo et al, 2011), chronic stress (Suvrathan et al, 2014), or during aging (Sametsky et al, 2010). Their formation involves de novo synaptogenesis and (or) removal of AMPAR from regular synapses (Hanse et al, 2013).…”
Section: Formation and Role Of Silent Synapsesmentioning
confidence: 99%